2013
DOI: 10.2337/dc12-1691
|View full text |Cite
|
Sign up to set email alerts
|

Atherosclerotic Disease in Type 2 Diabetes Is Associated With an Increase in Sclerostin Levels

Abstract: OBJECTIVEWnt/β-catenin signaling is related to the pathogenesis of several diseases. Sclerostin is an inhibitor of Wnt/β-catenin signaling. However, there are few data regarding the sclerostin levels and vascular disease. Our aim was to examine the relationship between serum sclerostin and atherosclerotic disease (AD) in type 2 diabetes mellitus (T2DM).RESEARCH DESIGN AND METHODSWe performed a cross-sectional study including 78 T2DM patients (45.3% females, mean age 59 ± 5.7 years; 54.7% males, 57.4 ± 6.7 year… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
79
8
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 117 publications
(95 citation statements)
references
References 35 publications
4
79
8
3
Order By: Relevance
“…Our first interesting and furthermore innovative result was that circulating sclerostin levels were significantly increased in women when compared with men with T1DM. With few exceptions (22), most of the existing data in the literature (23,24) showed higher sclerostin levels in men to an extent diametrically opposed with our findings; furthermore, they are based on studies involving subjects affected by T2DM (30). Even Gennari et al (16) showed higher sclerostin levels in men but the overall cohort also included T2DM subjects and healthy controls; for this reason, their results are not generalizable to T1DM.…”
Section: Discussioncontrasting
confidence: 93%
See 3 more Smart Citations
“…Our first interesting and furthermore innovative result was that circulating sclerostin levels were significantly increased in women when compared with men with T1DM. With few exceptions (22), most of the existing data in the literature (23,24) showed higher sclerostin levels in men to an extent diametrically opposed with our findings; furthermore, they are based on studies involving subjects affected by T2DM (30). Even Gennari et al (16) showed higher sclerostin levels in men but the overall cohort also included T2DM subjects and healthy controls; for this reason, their results are not generalizable to T1DM.…”
Section: Discussioncontrasting
confidence: 93%
“…In our study, women exhibited higher sclerostin levels and a lower prevalence of macroangiopathy when compared with men who, on the other hand, showed higher homocysteine levels. Sclerostin was negatively associated with homocysteine in the whole population of T1DM, in contrast to what has recently been observed in T2DM (30). These data may account for an increased cardiovascular risk in men in comparison with women with T1DM.…”
Section: Clinical Studycontrasting
confidence: 75%
See 2 more Smart Citations
“…Adjusting for potential confounders, sclerostin and Dkk-1 levels showed inverse significant association with CIMT. The negative association between sclerostin and CIMT contrasts with the findings by Morales-Santana et al 17 We used the same kits to measure sclerostin, and therefore, we do not believe that differences in the methodology for measuring sclerostin explain the differences in the findings from our study and that of Morales-Santana. Gender difference may influence association as sclerostin levels are higher in males compared with females.…”
Section: Discussioncontrasting
confidence: 84%